Variability in Myosteatosis and Insulin Resistance Induced by High-Fat Diet in Mouse Skeletal Muscles. (13th August 2014) - Collino, Massimo; Mastrocola, Raffaella; Nigro, Debora; Chiazza, Fausto; Aragno, Manuela; D'Antona, Giuseppe; Minetto, Marco A.
Abstract : Nutrient overload leads to impaired muscle oxidative capacity and insulin sensitivity. However, comparative analyses of the effects of dietary manipulation on skeletal muscles with different fiber composition are lacking. This study aimed to investigate the selective adaptations in the soleus and tibialis anterior muscles evoked by administration of high-fat diet for 12 weeks in 10 mice (HFD mice) compared to 10 animals fed with a normal chow diet (control mice). Mice fed with the HFD diet exhibited hyperlipidemia, hyperinsulinemia, hyperglycemia, and lower exercise capacity in comparison to control mice. In control mice, soleus fibers showed higher lipid content than tibialis anterior fibers. In contrast, the lipid content was similar between the two muscles in HFD mice. Significant differences in markers of muscle mitochondrial production and/or activity as well as of lipid synthesis were detected between HFD mice and control mice, especially in the tibialis anterior. Moreover, translocation of GLUT-4 transporter to the plasma membrane and activation of the insulin signaling pathway were markedly inhibited in the tibialis and slightly reduced in the soleus of HFD mice compared to control mice. Overall, these results show that adaptive responses to dietary manipulation occur in a muscle-specific pattern.